The Impact of Intensified Hemodialysis on Pruritus in an End Stage Renal Disease Patient with Biliary Ductopenia - Sandra Chomicki; Omar Dahmani (Case Reports in Nephrology)
We report a unique observation characterized by the coexistence of idiopathic adulthood ductopenia (IAD), a rare cholestatic disease, and end stage renal failure treated by conventional hemodialysis in a patient awaiting double renal and liver transplantation. As pruritus gradually worsened, we hypothesized that intensified dialysis could alleviate the symptoms. Conventional hemodialysis following 3 hours/3 times a week regimen was initiated in December 2013. Due to increasing pruritus not responding to standard medical therapy, intensified hemodialysis following 2.5 hours/5 times a week regimen was started in May 2014. During two weeks, a temporary decrease in bilirubin levels was observed. No major changes on other liver function tests and inflammatory markers occurred. Nevertheless, a persistent improvement on pruritus and general wellbeing was obtained during the four weeks’ study period. The pathogenesis of itch encompasses multiple factors, and, in our case, both uremic and cholestatic pruritus are involved, although the latter is likely to account for a greater proportion. By improving itch intensity, through better clearance of uremic and cholestatic toxins which we detail further, intensive dialysis appears to be an acceptable short-term method for patients with hepatic cholestasis and moderate pruritus not responding to conventional therapy. Additional studies are needed to assess and differentiate precisely factors contributing to pruritus of both origins.